Prospective study of a new endoscopic duodenal–jejunal bypass sleeve in obese patients with nonalcoholic fatty liver disease (with video). Issue 1 (23rd August 2022) - Ren, Mengting; Zhou, Xinxin; Yu, Mosang; Cao, Yang; Xu, Chengfu; Yu, Chaohui; Ji, Feng
Abstract : Objectives: To evaluate the safety and efficacy of a new endoscopic duodenal– jejunal bypass sleeve (DJBS) in obese patients with nonalcoholic fatty liver disease (NAFLD), while in situ for 3 months, and at 6 months postexplantation. Methods: Patients with obesity and NAFLD were enrolled in this single‐center, prospective study, wherein the TONGEE DJBS (Tangji Medical, Hangzhou, China) was implanted for 3 months. Primary outcomes were weight loss and changes in hepatic steatosis. Secondary outcomes included changes in liver enzymes, glycemic control, and lipid profile and device safety. Results: Twenty‐six patients (age 35.2 ± 7.2 years; 61.5% women) underwent DJBS implantation. At 3 months, bodyweight change from baseline was −8.0 ± 3.6 kg ( P  < 0.001), corresponding to 8.9 ± 4.0% of total bodyweight. Hepatic steatosis significantly improved based on controlled attenuation parameter, hepatic steatosis index, and fatty liver index ( P  < 0.001). Liver enzymes, insulin resistance, and metabolic parameters were also improved. At 6 months postexplantation, weight loss and improvements in hepatic steatosis and liver enzyme levels remained statistically significant. Only one patient had a serious adverse event, namely, upper gastrointestinal hemorrhage. Conclusions: Three‐month TONGEE DJBS implantation resulted in significant weight loss and improvement in hepatic steatosis, liver enzymes, insulin resistance, and metabolic parameters in obese patients with NAFLD. Randomized controlled trials are required to further elucidate these initial findings.